2021
DOI: 10.48550/arxiv.2107.13208
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimal gamma-ray selections for monochromatic line searches with DAMPE

Abstract: The DArk Matter Particle Explorer (DAMPE) is a space high-energy cosmic-ray detector covering a wide energy band with a high energy resolution. One of the key scientific goals of DAMPE is to carry out indirect detection of dark matter by searching for high-energy gamma-ray line structure. To promote the sensitivity of gamma-ray line search with DAMPE, it is crucial to improve the acceptance and energy resolution of gamma-ray photons. In this paper, we quantitatively prove that the photon sample with the larges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Our most recent simulations of GAMMA-400 energy resolution showed that realistically we can expect this sensitivity to be comparable to that of Fermi-LAT in the energy range ∼(0.1-100) GeV. At the same time DAMPE has comparable sensitivity too [30]. Hence the combined (stacked) data analysis from all three telescopes will potentially allow to significantly extend the range of probed diphoton annihilation cross sections.…”
Section: Introductionmentioning
confidence: 76%
“…Our most recent simulations of GAMMA-400 energy resolution showed that realistically we can expect this sensitivity to be comparable to that of Fermi-LAT in the energy range ∼(0.1-100) GeV. At the same time DAMPE has comparable sensitivity too [30]. Hence the combined (stacked) data analysis from all three telescopes will potentially allow to significantly extend the range of probed diphoton annihilation cross sections.…”
Section: Introductionmentioning
confidence: 76%
“…However our most recent simulations showed that the sensitivity presented in (Egorov et al, 2020) tends towards slightly optimistic siderealistically we would expect our sensitivity to be comparable with that of Fermi-LAT after 12-15 years of its operation. At the same time DAMPE has comparable sensitivity too (Zun-Lei Xu et al, 2021). Hence, it can be possible in the future to stack together the data from all three telescopes and significantly extend the sensitivity to narrow lines by such joint data analysis.…”
Section: Dark Matter Searchingmentioning
confidence: 99%